BETWEEN EMPIRE AND COLONY. MIŁOSZ AND DOSTOYEVSKI - Wedemann, Marek (Porównania, 2012)
The author puts Czesław Miłosz’s reflection of the phenomenon of Dostoyevski’s works in the context of postcolonial studies. He draws the attention to the innovative character and complementarity of the poet’s essays on Russian literature which is different to the its analysis carried out by Ewa M. Thompson in ”Imperial Knowledge. Russian Literature and Colonialism”.